Teater Sebagai Media untuk Pengabdian Masyarakat - Setefanus Suprajitno (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Theater is not just a performing art that has aesthetic function, as a phrase, art for art, reflects. It also has a connection with the social community outside the art world. In this paper, through the discipline of educational anthropology, I examine the use of theater as a medium for service-learning, a project I conducted in 2015-2016. In this project, students were asked to work together with members of community involved to write a script based on their experiences. This script is expected to reflect their understanding and interpretation on the social and cultural problems of the society where they lived. My analysis shows that theater as a medium for service-learning could give a valuable opportunity for students to foster their social responsibility and awareness. It also helps students understand the social problems of the society, and document their understanding through theatrical process. This results in developing the cultural agency of the students and members of community involved.